High-performance liquid chromatographic analysis of angiotensin II receptor antagonist valsartan using a liquid extraction method - Daneshtalab, Noriko; Lewanczuk, Richard Z; Jamali, Fakhreddin (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2002)
Purpose: To develop an easy assay for the quantitation of the angiotensin II receptor antagonist valsartan in human plasma using a liquid extraction procedure. Method: The method involves acid extraction from 1 ml human plasma with methyl- tert.-butyl ether followed by back-extraction into a basic medium. An isocratic HPLC equipped with reverse phase column and a fluorescence detector was used at room temperature. Results: The response to 10–2000 ng/ml valsartan was linear. In plasma of three human subjects given 160 mg valsartan orally, concentrations of 25–1540 ng/ml were observed. Conclusion: This convenient method is suitable for pharmacokinetic studies of valsartan.